Regionalizm frekwencyjny w badaniach historycznojęzykowych (część 1. Zarys problematyki badawczej) - Michalska, Paulina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The aim of the article is to draw attention to the complexity of studies into various frequency of occurrence of linguistic phenomena, conditioned regionally, and to stress that it is an initial stage of such research in Polish Language Studies. The article also reveals the necessity to arrive at more precise formulations on theoretical level, especially of an ambiguous definition of the term frequential regionalism for the needs of the history of the Polish language. The notion of frequential regionalism, existing in the literature on the subject, has been discussed, and also, the questions directly connected with this notion and not included in its definition (differences between particular regions in frequency of a given form, varied frequency of use within a region and the duration of a phenomenon). Also, some issues have been indicated not directly connected with the definition of the discussed notion, but appearing in the studies concerning frequency: the choice of a representative and proportional source base; the means of determining regional origin of printed texts; characteristics of statistical research.